Effects of Early Retirement Policy Changes on Working until Retirement: Natural Experiment - Boot, Cécile R.L. (Int J Environ Res Public Health, 2019)
Many European countries have implemented pension reforms to increase the statutory retirement age with the aim of increasing labor supply. However, not all older workers may be able or want to work to a very high age. Using a nation-wide register data of labor market transitions, we investigated in this natural experiment the effect of an unexpected change in the Dutch pension system on labor market behaviors of older workers. Specifically, we analyzed transitions in labor market positions over a 5-year period in two nation-wide Dutch cohorts of employees aged 60 years until they reached the retirement age (n = 23,703). We compared transitions between the group that was still entitled to receive early retirement benefits to a group that was no longer entitled to receive early retirement benefits. Results showed that the pension reform was effective in prolonging work participation until the statutory retirement age (82% vs. 61% at age 64), but also to a larger proportion of unemployment benefits in the 1950 cohort (2.0–4.2%) compared to the 1949 cohort (1.4–3.2%). Thus, while ambitious pension reforms can benefit labor supply, the adverse effects should be considered, especially because other studies have shown a link between unemployment and poor health.